Peripherally Infused Norepinephrine to Avoid Central Venous Catheter Placement in a Medical Intensive Care Unit: A Pilot Study. Issue 7 (July 2022) - Groetzinger, Lara M.; Williams, Julia; Svec, Susan; Donahoe, Michael P.; Lamberty, Phillip E.; Barbash, Ian J.
Background: Reducing central venous catheter (CVC) utilization can reduce complications in the intensive care unit (ICU). While norepinephrine (NE) is traditionally administered via a CVC, lower concentrations may be safely administered via peripheral intravenous (PIV) lines. Objective: We aimed to describe the implementation of a pilot protocol utilizing PIVs to administer a low-dose and lower-concentration NE, review the number of CVCs avoided, and evaluate any adverse events. Methods: In a quaternary medical intensive care unit (MICU), from March 1, 2019, to February 29, 2020, we reviewed charts for CVC placement and adverse events from the pNE infusion. We also measured unit-level CVC utilization in all MICU patients and assessed the change in utilization associated with the peripheral norepinephrine (pNE) protocol. Results: Over a 1-year period, 87 patients received a pNE infusion. Overall, 44 patients (51%) never required CVC placement during their MICU stay. Three patients (3%) experienced adverse events, none of which were documented as serious and or required antidote for treatment. Implementation of the protocol was associated with a decrease in the number of patients at the unit level who received CVCs, even if they did not receive pNE. Conclusion and Relevance: In this small pilot study, we pragmatically demonstrated that pNE is safe and may reduce the need for CVC placement. This information can be used to aid in pNE protocol development and implementation at other institutions, but further research should be done to confirm the safety of routine use of pNE in clinical practice.